2019
DOI: 10.1016/j.celrep.2019.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Dlk1-Mediated Temporal Regulation of Notch Signaling Is Required for Differentiation of Alveolar Type II to Type I Cells during Repair

Abstract: SUMMARY Lung alveolar type I cells (AT1) and alveolar type II cells (AT2) regulate the structural integrity and function of alveoli. AT1, covering ~95% of the surface area, are responsible for gas exchange, whereas AT2 serve multiple functions, including alveolar repair through proliferation and differentiation into AT1. However, the signaling mechanisms for alveolar repair remain unclear. Here, we demonstrate, in Pseudomonas aeruginosa -induced acute lung injury in mice, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 64 publications
(110 reference statements)
3
91
0
Order By: Relevance
“…Similar to our findings, that study showed that inadequate alveolar repair after acute injury contributed to increased fibrogenesis; in contrast to our findings, alveolar repair in the S pneumoniae model was dependent on both YAP and TAZ expression. Another recent study using a Pseudomonas aeruginosa acute infection model suggested a role for Dlk-1 in downregulating Notch signaling to promote AEC2-AEC1 differentiation (41). Thus, multiple developmental pathways, including Wnt, Hippo, and Notch, work together to mediate tissue repair after alveolar injury.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, that study showed that inadequate alveolar repair after acute injury contributed to increased fibrogenesis; in contrast to our findings, alveolar repair in the S pneumoniae model was dependent on both YAP and TAZ expression. Another recent study using a Pseudomonas aeruginosa acute infection model suggested a role for Dlk-1 in downregulating Notch signaling to promote AEC2-AEC1 differentiation (41). Thus, multiple developmental pathways, including Wnt, Hippo, and Notch, work together to mediate tissue repair after alveolar injury.…”
Section: Discussionmentioning
confidence: 99%
“…To study the mechanisms of alveolar repair, we used a mouse lung injury model generated by intratracheal injection (i.t.) of PA (Liu et al, 2011;Sadikot et al, 2006), which is characterized by severe inflammation and alveolar damage 24 to 48 h postinjury and AT2-mediated repair 3-7 days post-injury (Finn et al, 2019;Liu et al, 2015). Based on our previously described endothelial barrier reparative properties of S1P (Natarajan et al, 2013;Tauseef et al, 2008), we further tested the role of S1P as an angiocrine mediator of alveolar epithelial repair in the PA model.…”
Section: Angiocrine S1p Is Required For the Recovery Of Lung Injury Amentioning
confidence: 99%
“…Noticeably, this latter work also disclosed that unlike Notch1 or Notch3, which displayed increased levels, Notch2 was decreased in advanced tumors in the Kras G12D NSCLC model, where it furthermore displayed a tumor suppressor function through modulation of the Wnt/Ī²-catenin pathway [82]. Notch2 is the predominant receptor activated in AT2 cells and is required for their proliferation and maturation [7], and absence of the Wnt-downstream target Dlk1 (delta-like 1 homolog)-which also participates in lung development and inhibits endogenous Notch signaling-in AT2 cells during AT2 to AT1 repair-induced transition causes Notch activity upregulation and results in a stalled differentiation of AT2 to AT1 cells as well as in accumulation of an intermediate cell type [83]. While the observations above are discernibly contrasting in regard to an oncogenic role for Notch2 in NSCLC initiation and progression, the inductive exertion of transition states in AT2 cells [83] and its implication in EMT [79], as well as its predominant function in AT2 cell maturation and differentiation [7], and the fact that AT2 cells have been shown to functionally serve as cells-of-origin of NSCLC [63,84] (Figure 2), strongly warrants further exploration into the cell-specific, gain-and loss-of-function effects of this receptor in postnatal lung function and oncogenesis.…”
Section: Notch and Nsclcmentioning
confidence: 99%